Virtual Reality Digital Destination - Mahdzar, Mazlina; Sapawi, Humaira Fatiha; Abd Karim, Khairul Musfirah; Ramlee, Nurul Nabilah; Wan Mohamed Kahar, Wan Nur Izzah Ilyana; Yusoff , Siti Aishah (Multidisciplinary Applied Research and Innovation, 2021)
Virtual digital destination is a platform created for the tourists to gain more knowledge or information about the destination that they want to visit during Covid-19. This digital platform was created to minimize face-to-face communication between tourists and operators due to the pandemic that requires us to always stick with the Standard Operation Procedure (SOP). Besides, live virtual can also add knowledge about tourist places whether for students or tourists themselves. Tourist will be able to communicate and join live sharing sessions about the local places by subscribing to website created. By implementing this concept of combining digital and modern innovation, travel companies are able to reduce their operating costs.